Great Power Competition in the Arctic Region and Changing Regional Dynamics - Zain Hyder Shah (CISS Insight Journal, 2023)
The Arctic region is important because of its rich minerals and resources. Amid rising multi-polarity, the Arctic region is emerging as the new front for great power confrontation. Once considered the peripheral region of great power competition, the region now faces looming threats related to climate change and the competition among the United States of America, Russia, and China over the untapped resources of the Arctic region. Undoubtedly, most Arctic states have peacefully advanced their economic capabilities and they look determined to follow the same trends in the future. However, Washington’s 2021 Arctic Strategy, and Moscow’s expansion and modernization of military bases in the Arctic region, including Rogachevo on Novaya Zemlya, are ushering serious concerns. Moreover, China’s white paper on the Arctic, ascertaining its initiative of the Polar Silk Road, has alarmed the West. Washington has announced the beginning of its Willow Project in Alaska after years of pause in its development in the Arctic. Such dynamics can redefine the state of the political economy in the Arctic region. This research paper analyzes the attitudes of the US, China, and Russia and how their political and economic dealings shape the latest debate regarding the future of the Arctic region.